2009
DOI: 10.1002/jmr.956
|View full text |Cite
|
Sign up to set email alerts
|

Combining atomic force and fluorescence microscopy for analysis of quantum‐dot labeled protein–DNA complexes

Abstract: Atomic force microscopy (AFM) and fluorescence microscopy are widely used for the study of protein-DNA interactions. While AFM excels in its ability to elucidate structural detail and spatial arrangement, it lacks the ability to distinguish between similarly sized objects in a complex system. This information is readily accessible to optical imaging techniques via site-specific fluorescent labels, which enable the direct detection and identification of multiple components simultaneously. Here, we show how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…First, flatness and transparency of the sample, which we achieved by gluing a few layers of mica to a thin glass coverslip (6,20). The advantages over using only glass (4,30) or only mica (5) are the improved visibility of DNA and mechanical stability, respectively. Second, image registration with nanometer resolution requires nanometer-size fiducial markers unrelated to the analyzed molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, flatness and transparency of the sample, which we achieved by gluing a few layers of mica to a thin glass coverslip (6,20). The advantages over using only glass (4,30) or only mica (5) are the improved visibility of DNA and mechanical stability, respectively. Second, image registration with nanometer resolution requires nanometer-size fiducial markers unrelated to the analyzed molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This method is limited because identification of specific proteins in heterogeneous assemblies depends on distinct structural features, whereas most proteins have a similar globular shape. Molecular recognition in high-resolution SFM images can be achieved by combining SFM with a fluorescence microscope capable of single-fluorescence detection (4)(5)(6). By labeling individual proteins or single DNA molecules, it is possible to distinguish the position of different components in a highly resolved complex.…”
mentioning
confidence: 99%
“…Super-resolution localization techniques may be used to enhance mapping precision. 19,2124 The data acquired using these techniques lacks the high resolution of DNA sequencing but offers genomic context and is therefore ideal for aiding sequence assembly, when used in combination with DNA sequencing 2530 as well as analysis of genomic structural variations on the individual chromosome level. 31,32 …”
Section: Dna Sequencing and Optical Mappingmentioning
confidence: 99%
“…The combination of high resolution fluorescence microscopy with AFM (FIONA-AFM) allows the identification and the localization of fluorescent-tagged molecules such as proteins on topographic image. The strength of this technique was evaluated by the analysis of the interaction of the protein complex UvrA-UvrB, involved in the initiation of nucleotide excision repair pathway, with DNA, and the binding of RNAP on Escherichia coli DNA (Ebenstein et al, 2009;Fronczek et al, 2011). Both studies showed the correlation between optical and AFM signals, providing a proof of principle for combining structural details of multi-molecular complexes with dynamic information yielded by fluorescence.…”
Section: Next Generation Afm For the Study Of Specific Molecules In Bmentioning
confidence: 99%